(untitled) - Zook, Chris (Boston, Massachusetts, 2016)
The key insight from Zook and Allen's research is that managing these choke points requires a "founder's mentality"-an insurgent's clear mission and purpose, an unambiguous owner mindset, and a relentless obsession with the front line (behaviors typically embodied by a bold, ambitious founder)-to restore the speed, focus, and connection to customers, all of which are lost as companies grow. Based on the authors' decade-long study of companies in more than forty countries, any leader-not only a founder-can use a founder's mentality to overcome these predictable challenges and set their companies back on a path of sustainable growth. This book shows how, empowering leaders everywhere to control the destiny of their companies.
Keywords: Quản trị công nghiệp,Industrial management